2023
DOI: 10.1111/inm.13130
|View full text |Cite
|
Sign up to set email alerts
|

Grace under pressure: Mental health nurses' stories of resilience in practice

Abstract: Mental health nurses experience both organizational and practice‐related stressors in their work. Resilience is an interactive process of positive adaptation following stress and adversity. There is limited evidence on how personal resilience is applied to mental health nursing practice. The aim of this interpretive narrative study was to explore mental health nurses' stories of resilience in their practice for the purpose of gaining an understanding of resilience resources they draw on when dealing with chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This is the first qualitative study to report the experience and impacts of the COVID‐19 pandemic on the resilience of nurses working in mental health settings. The study builds on prior knowledge of nurses' capacity for positive adaptation to workplace challenges in mental health settings (Delgado et al, 2022; Foster et al, 2023; Foster, Cuzzillo, & Furness, 2018). New understandings of how mental health nurses' resilience was challenged and maintained during COVID‐19 are useful for addressing the enduring negative impacts of the pandemic on nurses' wellbeing and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is the first qualitative study to report the experience and impacts of the COVID‐19 pandemic on the resilience of nurses working in mental health settings. The study builds on prior knowledge of nurses' capacity for positive adaptation to workplace challenges in mental health settings (Delgado et al, 2022; Foster et al, 2023; Foster, Cuzzillo, & Furness, 2018). New understandings of how mental health nurses' resilience was challenged and maintained during COVID‐19 are useful for addressing the enduring negative impacts of the pandemic on nurses' wellbeing and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings share some similarity with those of generalist nurses, who used self‐regulation to manage anxiety and maintain a positive perspective when caring for patients with COVID‐19 (Huang et al, 2021), but the use of emotional regulation during COVID‐19 by nurses in mental health has not previously been documented. Previous qualitative studies with MHNs have reported nurses' use of emotional intelligence skills (e.g., emotional self‐regulation) to tackle workplace challenges such as emotional labour (Delgado et al, 2022) or complex interpersonal interactions (Foster et al, 2023). Wellbeing and resilience‐enhancing interventions that provide nurses with these emotional intelligence skills (Foster, Cuzzillo, & Furness, 2018; Foster, Shochet, et al, 2018) can be useful strategies to support nurses' personal wellbeing and practice against future adversities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations